2014
DOI: 10.5588/ijtld.13.0519
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and clinical role of rapid C-reactive protein testing in HIV-infected individuals with presumed tuberculosis in South Africa

Abstract: Objective We sought to determine the accuracy and role of rapid C-reactive protein (CRP) testing in HIV-infected tuberculosis suspects. Design We enrolled HIV-infected adults (≥18 years) with a cough for ≥2 weeks and negative sputum smears for acid-fast bacilli (AFB) in KwaZulu-Natal, South Africa. Participants were evaluated for pulmonary tuberculosis by a nurse with rapid CRP, and independently by a physician with a chest radiograph. Rapid CRP test results were compared to laboratory CRP and sputum sent fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 26 publications
1
58
1
1
Order By: Relevance
“…One study evaluated two different CRP assays (POC sandwich vs. lab-based immunoturbidometric assay) within the same study population and found no differences in their diagnostic accuracy for pulmonary TB. 28 To avoid underestimating heterogeneity, we included accuracy data obtained from only the POC assay. 28 None of the included studies reported enrolling pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study evaluated two different CRP assays (POC sandwich vs. lab-based immunoturbidometric assay) within the same study population and found no differences in their diagnostic accuracy for pulmonary TB. 28 To avoid underestimating heterogeneity, we included accuracy data obtained from only the POC assay. 28 None of the included studies reported enrolling pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
“…28 To avoid underestimating heterogeneity, we included accuracy data obtained from only the POC assay. 28 None of the included studies reported enrolling pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of assays are available to measure this because of the use of CRP in cardiovascular disease. In a recent study, rapid CRP >8 mg/dl had a sensitivity of 95% and specificity of 51% for the diagnosis of TB in symptomatic HIV-infected persons with negative sputum smears [141]. Neopterin is produced by activated macrophages and dendritic cells.…”
Section: Nonspecific Biomarkersmentioning
confidence: 99%
“…Despite its discovery in 1930 (Tillett & Francis, 1930), CRP continues to be investigated for its diagnostic and prognostic utility. Recent examples include periprosthetic joint infection (Deirmengian et al, 2014), urinary tract infections (Xu, Liu, Liu, & Dong, 2014), tuberculosis in HIV patients (Drain et al, 2014), and as an early predictor of infective complications in laparoscopic colorectal surgery (Nason et al, 2014).…”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%